Alexandre de la Charme’s Chinese–Manchu Treatise Xingli zhenquan tigang (Sing lii jen ciyan bithei hešen) in the Early Entangled History of Christian, Neo-Confucian, and Manchu Shamanic Thought and Spirituality as Well as Early Sinology - David Bartosch (Religions, 2025)
The work Xingli zhenquan tigang (Sing lii jen ciyan bithei hešen) was written in Chinese and Manchu by the French Jesuit Alexandre de la Charme (1695–1767) and published in Beijing in 1753. The first two sections of this paper provide an introduction to de la Charme’s work biography and to further textual and historical contexts, explore the peculiarities of the subsequent early German reception of the work almost 90 years later, and introduce the content from an overview perspective. The third section explores the most essential contents of Book 1 (of 3) of the Manchu version. The investigation is based on Hans Conon von der Gabelentz’s (1807–1874) German translation from 1840. Camouflaged as a Confucian educational dialogue, and by blurring his true identity in his publication, de la Charme criticizes Neo-Confucian positions from an implicitly Cartesian and hidden Christian perspective, tacitly blending Cartesian views with traditional Chinese concepts. In addition, he alludes to Manchu shamanic views in the same regard. De la Charme’s assimilating rhetoric “triangulation” of three different cultural and linguistic horizons of thought and spirituality proves that later Jesuit scholarship reached out into the inherent ethnic and spiritual diversity of the Qing intellectual and political elites. Hidden allusions to Descartes’s dualistic concepts of res cogitans and res extensa implicitly anticipate the beginnings of China’s intellectual modernization period one and a half centuries later. This work also provides an example of how the exchange of intellectual and religious elements persisted despite the Rites Controversy and demonstrates how the fading Jesuit mission influenced early German sinology. I believe that this previously underexplored work is significant in both systematic and historical respects. It is particularly relevant in the context of current comparative research fields, as well as transcultural and interreligious intellectual dialogue in East Asia and around the world.